2020
DOI: 10.1002/ajoc.202000213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Electrochemical Properties of Polymers Based on Dithienothiophene and Bithiazole

Abstract: Conjugated polymers are promising cost‐effective, lightweight, and flexible electrode materials. 3,5‐Dinonyl‐2,6‐di(thiophene‐2‐yl)dithieno[3,2‐b : 2′,3′d]thiophene (M1) as a donor and 4,4′‐dinonyl‐5,5′‐di(thiophen‐2‐yl)‐2,2′‐bithiazole (M2) as an acceptor were synthesized and their polymers poly(3,5‐dinonyl‐2,6‐di(thiophene‐2‐yl)dithieno[3,2 b : 2′,3′‐d]thiophene) (P1) and poly(4,4′‐dinonyl‐5,5′‐di(thiophen‐2‐yl)‐2,2′‐bithiazole) (P2) were obtained via electropolymerization on ITO/glass electrode surface in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Fiber forming thiophene fluorophores 1-3 as well as nonfiber forming DTTO-SO and DTTO-NCS are characterized by the presence of the rigid three annulated core DTTO, which is an important building block for the preparation of organic functional materials. [30] Fluorophores 4-6 can instead be viewed as derivatives of terthiophene, which is also a well-known building block for the preparation of conjugated materials. [31,32] The first example of formation of the microfibers described here goes back to a decade ago when it was reported that live mouse 3T3 fibroblasts treated with a solution of the green emitting cell-permeant and cytocompatible fluorophore DTTO-1 spontaneously formed intracellular fluorescent and electroactive nanostructured microfibers mostly composed of collagen type-1 and…”
Section: The Formation Of Microfibers: a Physiological Live Cell Guid...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber forming thiophene fluorophores 1-3 as well as nonfiber forming DTTO-SO and DTTO-NCS are characterized by the presence of the rigid three annulated core DTTO, which is an important building block for the preparation of organic functional materials. [30] Fluorophores 4-6 can instead be viewed as derivatives of terthiophene, which is also a well-known building block for the preparation of conjugated materials. [31,32] The first example of formation of the microfibers described here goes back to a decade ago when it was reported that live mouse 3T3 fibroblasts treated with a solution of the green emitting cell-permeant and cytocompatible fluorophore DTTO-1 spontaneously formed intracellular fluorescent and electroactive nanostructured microfibers mostly composed of collagen type-1 and…”
Section: The Formation Of Microfibers: a Physiological Live Cell Guid...mentioning
confidence: 99%
“…Fiber forming thiophene fluorophores 1‐3 as well as non‐fiber forming DTTO‐SO and DTTO‐NCS are characterized by the presence of the rigid three annulated core DTTO, which is an important building block for the preparation of organic functional materials. [ 30 ] Fluorophores 4‐6 can instead be viewed as derivatives of terthiophene, which is also a well‐known building block for the preparation of conjugated materials. [ 31,32 ]…”
Section: The Formation Of Microfibers: a Physiological Live Cell Guid...mentioning
confidence: 99%
“…Moreover, in continuation of the development of DTT-based polymers, 68 the same group has also synthesized bithiazole and DTT-based polymers 39, 40, and 41 – exhibiting excellent optical and electronic properties ( Scheme 5 ). 69 In this particular study, the they first synthesized a donor 35 (3,5-dinonyl-2,6-dithiophenyl-DTT), and an acceptor 38 (nonylbithiazole), as shown in Scheme 5 . Later on, self electropolymerization of 40 and 43 by virtue of the cyclic voltammetry afforded the polymers 39 and 40 ( Scheme 5 ).…”
Section: Dtt-based Molecules and Their Potential Applicationsmentioning
confidence: 99%
“…Additionally, they revealed from the DFT calculations, an intramolecular charge transfer from the donor (DTT) towards the acceptor (boron). From the TD-DFT calculations, they noticed the vertical excitations (HOMO to LUMO) and emissions (LUMO to HUMO).Moreover, in continuation of the development of DTT-based polymers,68 the same group has also synthesized bithiazole and DTT-based polymers 39, 40, and 41exhibiting excellent optical and electronic properties (Scheme 5) 69. In this particular study, the they rst synthesized a donor 35(3,5-dinonyl-2,6dithiophenyl-DTT), and an acceptor 38 (nonylbithiazole), as shown in Scheme 5.…”
mentioning
confidence: 99%
“…Conducting polymers have gained a lot of interest in the area of optoelectronics because of advantages such as low cost, tunability of optical properties, lightweight nature and flexibility (Dikcal et al, 2020). The properties of conjugated polymers can be tweaked either through modification of the side chains or the main chain (Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%